Instilling the Values of Ahlus Sunnah Wal Jama’Ah An-Nahdiliyah Through Islamic Religious Education - Syafira, Alda; Rodliyah, St.; Mursalim, Mursalim (Institut Agama Islam Negeri (IAIN) Curup, 2023)
This study aims to identify Ahlussunnah Wal Jama’ah An-Nahdliyyah efforts to inculcate the values through Islamic religious education. This study used qualitative research by conducting research in Madrasah. The method of data collection is through observations, interviews and taking strong approaches to students, while data analysis using the Miles and Huberman method shows that in qualitative analysis, it is done interactively and continuously, especially by reducing, displaying data and counting, plotting or verifying. The results of this study indicate that the inculcation of the values of Ahlussunnah Wal Jama’ah An-Nahdliyyah is achieved through Islamic religious education materials, while attempting to inculcate the attitudes of tawasut, tawazun, tasammuh and amar ma’ruf nahi mungkar. They are students with good morals, tolerance, humanity, humility, and interaction in daily life.